PENGARUH MEDIA AUDIO VISUAL (FILM ANIMASI) TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TK GBKP TUNAS HARAPAN KOTA PEKANBARU - Desiana Widiawati Br Sitepu; Wusono Indarto; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the research which is conducted at children age 5-6 year at GBKP Tunas Harapan Kindergarten is the low of children’s scrutinize. The research aims to prove that there is an effect of Audio Visual Media (Film Animation) for the skill scrutinize. This research used quantitative research by using experiment and one group pretest-posttest design. The subjects of the research are 18 childrens. The data collecting method used are observation and documentation. The data analysis used is parametric statistics test, t-test related by using SPSS Windows ver 22. Based on the result of the data analysis about the ability scrutinize in the first observation (pre-test) and the observation conducted after the treatment (post-test) by used audio visual media (film animation)earned value tarithnetic = 26,113 and value ttable = 2,110. It can be seen the price tarithnetic = 26,113 greather than ttable = 2,110. The conclusion of research shows that audio visual media (film animation) affect the age 5-6 years group children’s scrutinize skill at TK GBKP Tunas Harapan kindergarten, it is proven that the audio visual media (film animation) can help the children in training their scrutinize skill.Key Words: Audio Visual Media (Film Animation), Scrutinize Skill